Income Creation by Means of Income Taxation - Hubbard, Joshua C. (Quarterly Journal of Economics, 1944)
I. Conditions under which taxation is income creating, 265. — Influence of expenditures, 268. — II. Under-employment equilibrium with consumption 100 per cent of income, 269. — III. Under-employment equilibrium with net investment and the average propensity to consume less than 100 per cent, 275. — IV. Full employment and a sudden closing of investment outlets, 280. — V. Application of the foregoing analysis in a practical program, 285. — Effectiveness of the income tax as an instrument of policy, 286.